The diagnosis and treatment of spasticity : a practical guide - Dones, Ivano; Levi, Vincenzo (Cambridge Scholars Publishing, 2019)
This volume is an updated practical guide to the diagnosis and treatment of spasticity, authored by experienced physicians with different specialties. It will help both GPs and specialists, through its provision of a number of tips and tricks to safely provide patients with the most convenient treatment of their spasticity.